Pemanfaatan Internet dalam Pembelajaran Bahasa Inggris oleh Guru Sekolah Menengah Kejuruan Negeri 1 Palangka Raya - Elmayantie, Catharina (STMIK Palangkaraya, 2018)
This study aims to see how the use of the internet and the problem in teaching faced by English teachers of SMK Negeri 1 Palangka Raya. This study is a descriptive study with a qualitative approach. There were 6 (six) English teachers taken as the subject of the study. In collecting data, the writer used direct observation, questionnaries, and documentation. The data reduction, data display and conclusion drawing applied for data analysis. The findings show most of the English teachers have been familiar with internet as a media and its function. They agreed that existance of internet technology is very helpful in teaching process and hardly needed to support teaching learning activities especially English language subject. Meanwhile, the problem faced by the teachers is the internet technology has not been used (secara maksimal) as the teaching media. Lack of maximum use of computer laboratory and networks to be used by all teacher and students’ activities is a major obstacle in terms of utilization of this technology.